PENGEMBANGAN MEDIA MOONSTAR (MONOPOLI SUPER PINTAR) PADA TEMA 2 KELAS IV MI AL-FIRDAUS BANDUNG - Siti Ghaida Sri Afira Ruhyadi (Limas PGMI, 2021)
This research was tried in grade IV MI Al-Firdaus Bandung aims to improve education using media facilities Domino smart in thematic subjects "Always Save Energy". This research listed the type of R&D development through the research stage using the ADDIE coverage model. Information collection includes Analysis, Design, Development, Implementation, and Evaluation sessions. From the form of this research creates data information with results by media experts get a value of 92% with very good criteria after that, the results of the module expert get a value of 83% with a good criteria value once. There is also a poll of teachers' reactions to the defense media that researchers have spread to get an average score of 91% which means the criteria are very good. The next stage of student results assessment with the use of extraordinary smart domination media gets a gain score of 0.51. Until it can be taken asimion through the development of educational media domination is amazingly smart able to improve learning outcomes and can be used like an educational media.